Effect of uniaxial stress on dielectric properties of 0-3 PZT-Portland cement composite - N. Jaitanong (2018)
The effects of uniaxial stress on the 0-3 lead zirconate titanate (PZT)-portland cement (PC) composite were investigated. PZT and PC composites were fabricated using 50% of PZT by volume. At room temperature, the dielectric properties were measured under stress free and stress level up to 57 MPa at the frequency of 1-100 kHz. The results showed that the dielectric constant of 0-3 PZT-PC composite was found to increase slightly from 169 to 188 (1 kHz) and 56 to 80 (100 kHz) in 0-3 PZT-PC composites under stress-free and stress up to 57 MPa, while dielectric loss tangent remained similar with increasing applied stress. Copyright © Taylor & Francis Group, LLC.